The relationship between firm size and volatility of stock returns - Freire, Beatriz Franco Paralta da Silva (2020)
The relationship between risk and returns its already very popular in financial markets, being the center of hundreds of studies nowadays. Within this wide range of researches, the firm size presents some impact on this relationship, being the smaller firms considered more risky and therefore, tending to reward investors with higher returns. But after all, to what extent is the firm size related with the volatility of such returns? Until today, few authors focused on this topic, motivating our study. In representation of the small and large firms we considered the Russell 2000 and Russell 1000 indexes and concluded that the behavior of the returns differs between these two types of firms. According to our empirical evidence, the small firms are more volatile on the short-run, while the larger firms appear to be more affected by the shocks in a long-term perspective. Quite surprisingly, the negative shocks seem to affect more large firms than the smaller firms. Additionally, we focused our attention on the volatility spillovers across firms and, through the analysis of the FEVD, we concluded that the error variance of the Russell 1000 contributes to explain the error variance of the Russell 2000 in 84.78849%. Based on the DCC model, we confirmed the presence of volatility transmissions, since the conditional correlation tend to increase in periods of crisis.